Effect of oral antihyperglycemic drugs on purine metabolism - T. S. Panevin (Endocrinology Research Centre, 2021)
Gout and diabetes mellitus are metabolic diseases, the pathogenesis of which is based on an excess of organic molecules in the body, in the first case — uric acid (UA), in the second — glucose. It is assumed that UA can also be involved in the pathogenesis of type 2 diabetes mellitus (T2DM), while insulin resistance and hyperglycemia affect purine metabolism. Both diseases are associated with an increased risk of cardiovascular events. In addition, chronic microcrystalline inflammation, which is absent in asymptomatic hyperuricemia, but is an obligatory component of gout, is probably an independent factor in T2DM, arterial hypertension, and cardiovascular events. The treatment of both diseases is strategically similar: in gout, the goal is to achieve a normal blood MC level, in T2DM — to normalize glycemia, and the frequent combination of these metabolic diseases requires taking into account the effect of drug therapy on concomitant diseases. Most modern antihyperglycemic drugs can affect purine metabolism, which is confirmed by the results of a number of foreign works. At the same time, the effect of T2DM therapy on purine metabolism and gout has not been adequately covered in the domestic literature, which was the purpose of this review.